Input database related uncertainty of Biome-BGCMuSo agro-environmental model outputs. Issue 11 (2nd November 2021) - Fodor, Nándor; Pásztor, László; Szabó, Brigitta; Laborczi, Annamária; Pokovai, Klára; Hidy, Dóra; Hollós, Roland; Kristóf, Erzsébet; Kis, Anna; Dobor, Laura; Kern, Anikó; Grünwald, Thomas; et al.
ABSTRACT: Gridded model assessments require at least one climatic and one soil database for carrying out the simulations. There are several parallel soil and climate database development projects that provide sufficient, albeit considerably different, observation based input data for crop model based impact studies. The input database related uncertainty of the Biome-BGCMuSo agro-environmental model outputs was investigated using three and four different gridded climatic and soil databases, respectively covering an area of nearly 100.000 km 2 with 1104 grid cells. Spatial, temporal, climate and soil database selection related variances were calculated and compared for four model outputs obtained from 30-year-long simulations. The choice of the input database introduced model output variability that was comparable to the variability the year-to-year change of the weather or the spatial heterogeneity of the soil causes. Input database selection could be a decisive factor in carbon sequestration related studies as the soil carbon stock change estimates may either suggest that the simulated ecosystem is a carbon sink or to the contrary a carbon source on the long run. Careful evaluation of the input database quality seems to be an inevitable and highly relevant step towards more realistic plant production and carbon balance simulations.